2018
DOI: 10.1161/jaha.118.010677
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome and Prognostic Factors of Complications in Thromboangiitis Obliterans (Buerger's Disease): A Multicenter Study of 224 Patients

Abstract: Background Data regarding long‐term outcome of patients with thromboangiitis obliterans are lacking and most series come from India and Japan. In this study, we assess long‐term outcome and prognostic factors in a large cohort of thromboangiitis obliterans. Methods and Results Retrospective multicenter study of characteristics and outcomes of 224 thromboangiitis obliterans patients fulfilling Papa's criteria were analyzed. Factors associated with vascular events and amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 18 publications
1
59
1
6
Order By: Relevance
“…Despite the rarity of TAO diagnoses in women, the proportion of women diagnosed with TAO has been reported to range between 10% and 23%. 1,[18][19][20][21][22] In the present study, there was difference in the proportion of males and females in the BM-MNC implantation and historical control groups. Data for these patients was obtained from the Hiroshima University Hospital database.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Despite the rarity of TAO diagnoses in women, the proportion of women diagnosed with TAO has been reported to range between 10% and 23%. 1,[18][19][20][21][22] In the present study, there was difference in the proportion of males and females in the BM-MNC implantation and historical control groups. Data for these patients was obtained from the Hiroshima University Hospital database.…”
Section: Methodsmentioning
confidence: 88%
“…21 Indeed, although Le Joncour et al reported that 10-year vascular event-free and amputation-free rates were 23% and 74%, respectively, in patients with TAO, there were only 3 unknown deaths reported (1.3%) and there was no cardiovascular death during long follow-up periods. 18 In addition, Guo et al reported that cell therapy improved the amputation-free survival rate over a 10-year follow-up period in Chinese patients with TAO who underwent BM-MNC implantations compared with the control group and that there were no deaths, major adverse cardiac events, or malignancy in the 2 groups during the follow-up period. 25 These findings suggest that increases in cardiovascular events, including limb amputation, are not related to the increase in mortality rate in TAO patients with and without cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The simplest and most effective method to prevent further aggravation of this diseases is to stop smoking completely or use tobacco in any form (151,152). After the diagnosis of TAO, patients who stop smoking have a lower risk of amputation than those who continue to smoke (153).…”
Section: Smoking and Thromboangiitis Obliterans Clinical Evidencementioning
confidence: 99%
“…Although the clinic-pathological hallmarks, and some molecular mechanisms have been studied, the etiology, pathophysiology, and optimal therapy remain not yet fully defined or understood [4]. Although a significant relationship between smoking (both tobacco and cannabis products) and progression of WBD has been identified [5], smoking per se cannot explain the prevalence and distribution of this harmful vascular disease [6]. Despite efforts in previous years and advances in medical therapy [4,7,8], WBD patients may actually benefit only by blocking smoking habits (abstinence of all tobacco/cannabis product use) and through targeted endovascular therapy, effective for preserving limb loss/amputation, and useful for accelerating the healing process in Buerger's ischemic ulcers [9].…”
Section: Introductionmentioning
confidence: 99%